Pengaruh Kepuasan Kerja Dan Komitmen Organisasi Terhadap Kinerja Karyawan (Studi Pada Rumah Sakit Bethesda Yogyakarta) - Purnama Novianta; Didik Subiyanto (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2020)
The purpose if this study is to describe (1) The effect of job satisfaction on employee performance at Bethesda Hospital in Yogyakarta, (2) Effect of organizational commitment on employee performance at Bethesda Hospitasl Yogyakarta, (3) the effect of work and organizational commitment on employee performance.Population in Bethesda Hospital employees in Yogyakarta with 1,200 employees. The taking technique uses a saturated sampling method for 120 respondents. The method of data collection uses a questionnaire, while the data analysis technique uses multiple regression analysis supported by the F test (F-test) and T test (T-test) and classic assumption test consisting of multicollinearity test, normality test, heteroscedasticity test.The results of the study obtained multiple linear regression equations for two variables are KIK = 6.183 + 0.734 KK + 3.151KO. So the results of the study show the effect of independent variables namely job satisfaction and organizational commitment on the dependent variable, namely employee performance(1) Variable job satisfaction is a variable that affects employee performance with a positive and significant regression coefficient of 0.734. This shows that every increase in employee job satisfaction will also improve employee performance2) Variable organizational commitment is a variable that affects employee performance with a positive and significant regression coefficient of 3.151. This shows that any increase in organizational commitment will also improve employee performance. (3) There is a significant positive effect of the influence of job satisfaction and organizational commitment on employee performance. The magnitude of the effect is determined by the terminated coefficient value (adjusted R2). The value of the coefficient of determination (adjusted R2) through regression analysis is 0.191, meaning that the independent variables together affect the dependent variable by 19.1% and the remaining 80.8% is influenced by other variables not included in the research model.